2013
DOI: 10.3126/ajn.v1i0.7545
|View full text |Cite
|
Sign up to set email alerts
|

Participatory variety slection of cold tolerant rice in the western hills of Nepal

Abstract: To verify and up scale promising cold tolerant rice genotypes in the western hills, participatory variety selection (PVS) activities viz; coordinated farmer's field trials (CFFTs), FFTs prepared from Lumle , farmers' acceptance tests (FATs), larger plot demonstrations, and upscaling activities were conducted during 2008 to 2009. Yield and yield related parameters considering farmers' preferences were also recorded and analyzed for PVSs under FATs. In 2008, genotypes NR10481-B-11-1-1-1, NR10479-B-33-2-1-1 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…According to a study by Karki et al, farmers in Nepal have thus far embraced Chhomrong, Machhapuchre-3, Chandannath-1, Chandannath-3, and Palung-2 as cultivars that tolerate cold conditions. The Chhomrong variety has become the most significant variety in Madagascar and Bhutan [76].…”
Section: Alleviation Of Flashmentioning
confidence: 99%
“…According to a study by Karki et al, farmers in Nepal have thus far embraced Chhomrong, Machhapuchre-3, Chandannath-1, Chandannath-3, and Palung-2 as cultivars that tolerate cold conditions. The Chhomrong variety has become the most significant variety in Madagascar and Bhutan [76].…”
Section: Alleviation Of Flashmentioning
confidence: 99%
“…On the other hand, Tainan-1, Chainan-2, Chainung-242, Taichung-176, Himali, Kanchan, Khumal-2, Khumal-3, Khumal-4, Khumal-5, Khumal-6, Khumal-7, Khumal-8, Khumal-9 and Manjushree 2 have been released for foot hills to mid hills of warm temperate areas of Nepal. Karki et al (2010) reported that Chhomrong dhan, Machhapuchre-3, Chandannath-1 and Chandannath-3 and Palung-2 have been adopted so far by farmers in Nepal as chilling tolerant cultivars. Chomrong rice of Nepal has become the most important variety in Bhutan and Madagascar covering around 85% of their rice area.…”
Section: Variety Released Worldwidementioning
confidence: 99%
“…For high hill and temperate conditions (2500-m and above) cold tolerant rice varieties of Chandannath-1 & 3 and other have been developed and popularized especially in Jumla and Karnali regions (Paudel, 2011) where there is acute shortage of food and around 3.9 million people in the area suffered from hunger and malnutrition (Paudel, 2010). Similarly, rice varieties Machhapuchhere-3 and Chhomrong Local have been popularized in upper high hills of more than 2000-m (Karki, et al, 2010). Likewise, improved varieties of maize, wheat, maize, tomato and potato have been developed to address situation brought about by climate change such as emergence of new insects, pests and diseases and natural disasters of flood, drought, hail storm and many more.…”
Section: Nepal's Efforts To Address Climate Changementioning
confidence: 99%